Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.14245/ns.1938222.111
|View full text |Cite
|
Sign up to set email alerts
|

Ossification of the Posterior Longitudinal Ligament: Surgical Approaches and Associated Complications

Abstract: Ossification of the posterior longitudinal ligament (OPLL) is a rare but potentially devastating cause of degenerative cervical myelopathy (DCM). Decompressive surgery is the standard of care for OPLL and can be achieved through anterior, posterior, or combined approaches to the cervical spine. Surgical correction of OPLL via any approach is associated with higher rates of complications and the presence of OPLL is considered a significant risk factor for perioperative complications in DCM surgeries. Potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 75 publications
(159 reference statements)
1
49
1
Order By: Relevance
“…2,16,17 In our study, 2 patients reported axial pain, which was effectively alleviated at 6 months postoperatively, similar to that noted in previous reports. 2,17 C5 palsy, another common complication of cervical laminoplasty, with incidence rates between 0% and 13.6%, may develop due to posterior decompression, leading to spinal cord shifting with resultant traction on the spinal cord and/or nerve roots. 18 In the present study, one patient who underwent hybrid decompression procedures and foraminotomy, with improvement of C2-C7 angle from À17.0 to 5 , had C5 palsy that was resolved at 9 postoperative months through rehabilitation.…”
Section: Discussionsupporting
confidence: 90%
“…2,16,17 In our study, 2 patients reported axial pain, which was effectively alleviated at 6 months postoperatively, similar to that noted in previous reports. 2,17 C5 palsy, another common complication of cervical laminoplasty, with incidence rates between 0% and 13.6%, may develop due to posterior decompression, leading to spinal cord shifting with resultant traction on the spinal cord and/or nerve roots. 18 In the present study, one patient who underwent hybrid decompression procedures and foraminotomy, with improvement of C2-C7 angle from À17.0 to 5 , had C5 palsy that was resolved at 9 postoperative months through rehabilitation.…”
Section: Discussionsupporting
confidence: 90%
“…Surgical intervention has demonstrated considerable efficacy in improving clinical outcomes for patients with myelopathy as a result of cervical or thoracolumbar OPLL [ 6 , 14 ]. The degree of myelopathy, determined by clinical symptom severity, is associated with the potential benefit of surgery with severe cases showing benefit from surgery, while medical management offers the same benefit as surgery for those with minimal symptoms [ 6 , 15 ]. For those treated conservatively, however, the risk for significant spinal cord injury causing significant disability remains markedly elevated [ 6 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The degree of myelopathy, determined by clinical symptom severity, is associated with the potential benefit of surgery with severe cases showing benefit from surgery, while medical management offers the same benefit as surgery for those with minimal symptoms [ 6 , 15 ]. For those treated conservatively, however, the risk for significant spinal cord injury causing significant disability remains markedly elevated [ 6 , 16 ]. Reported surgical applications for OPLL aim to decompress the spinal cord and subsequently stabilize the spinal column via different approaches including anterior cervical discectomy and fusion, posterior laminectomy and fusion, posterior laminoplasty, and circumferential approaches such as posterior circumferential decompression [ 6 , 7 , 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoracolumbar spinal fractures complicated with spinal cord injury serverely negatively impact the quality of life of patients [ 8 , 9 ]. The T 11 –L 2 spine segment is the intersection of physiological curvature of the thoracic and lumbar vertebrae, with concentrated stress, a small range of motion, and a narrow spinal canal, which has a high risk of spinal cord and/or cauda equina injury after fractures [ 10 ]. Spinal cord and cauda equina injuries result in limb sensory and motor dysfunction or even paralysis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%